Analisis Unsur Intrinsik Puisi Karya Peserta Didik Kelas IV A SD Supriyadi Semarang - Haliza, Anisa Nurul; Huda, Choirul; P, Agnita Siska (TSAQOFAH, 2023)
This research was motivated by the researcher's curiosity about the ability to write free poetry by students in class IV A at SD Supriyadi Semarang. The thing identified as one of the problems in the focus of this research is students' ability to write poetry based on intrinsic elements of poetry that have not been implemented. The aim of the research is to describe the intrinsic elements of poetry by class IV A students at SD Supriyadi Semarang. which focuses on five intrinsic elements only, namely theme, diction, rhyme, feeling and message. The subjects in this research were 28 students in class IV A of SD Supriyadi Semarang with research objects in the form of 6 poetry texts which were created in groups consisting of 6 groups according to creative ideas, experiences, stories, the surrounding environment and the conditions of the participants. educate yourself. This research was prepared and carried out using descriptive methods through a qualitative approach. The data collection techniques used were documentation and tests. Based on the data collection and discussion of the analysis results, it was found that 100% of the poems written by the students were correct, namely 3 poems and the other 3 poems were mostly 93% correct.